2012
DOI: 10.1371/journal.pone.0044555
|View full text |Cite
|
Sign up to set email alerts
|

Transitory versus Persistent Effects of Connectivity in Environmentally Homogeneous Metacommunities

Abstract: While the effect of habitat connectivity on local and regional diversity has been analysed in a number of studies, time-dependent dynamics in metacommunities have received comparatively little consideration. When local patches of a metacommunity are identical in environmental conditions but differ in initial community composition, dispersal among patches may result in homogenization of local communities. In a microcosm experiment with benthic ciliates, we tested the hypothesis that the effect of connectivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 37 publications
4
26
0
Order By: Relevance
“…Community assembly involves multiple ecological processes operating at different spatial scales (Ricklefs , Brown 2014). At local scales, physical environmental factors, such as soil properties and topography, play critical roles in the assembly of ecological communities (Weiher and Keddy , De Cáceres et al ). For example, Cornwell and Ackerly () found that plant traits showed a close relationship with topography and soil moisture in a coastal landscape in California.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Community assembly involves multiple ecological processes operating at different spatial scales (Ricklefs , Brown 2014). At local scales, physical environmental factors, such as soil properties and topography, play critical roles in the assembly of ecological communities (Weiher and Keddy , De Cáceres et al ). For example, Cornwell and Ackerly () found that plant traits showed a close relationship with topography and soil moisture in a coastal landscape in California.…”
Section: Introductionmentioning
confidence: 99%
“…Habitat fragmentation transforms large expanses of habitat into numerous smaller patches of lower total area, isolated from each other by a matrix of habitats unlike the original (Wilcove et al 1986). Habitat fragmentation thus alters both the total amount and the spatial configuration of remaining habitat (Didham et al ). Widespread fragmentation means that the majority of local community dynamics now takes place within small habitat fragments in close proximity to anthropogenic edges (Broadbent et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations